Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan - Alfina Sri Rahayu Diana Novita Sari; Indah Rizki Maulia; Raudhatul Hikmah; Suci Indah Lestari (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
This research summarizes findings from related journal literature to investigate the impact of work motivation and discipline on employee performance. Through a literature review, this article outlines the positive relationship between intrinsic and extrinsic motivation and employee performance, as well as the role of work discipline in increasing efficiency and effectiveness in the workplace. The various empirical studies reviewed show that a high level of motivation and a strong level of work discipline can create more productive and high-performing employees. Literacy also highlights the importance of integrating human resource management strategies that focus on increasing motivation and implementing effective work discipline. This research provides an in-depth understanding of these concepts and emphasizes their relevance in the modern organizational context. In conclusion, this article provides a practical view for human resource management in improving employee performance.